ANALISIS KESTABILAN PADA MODEL FITO-ZOOPLANKTON DENGAN WAKTU TUNDA PADA ZOOPLANKTON DI KOLAM STABILISASI LIMBAH - GESTI ESSA WALDHANI (Universitas Negeri Surabaya, 2025)
In this paper, we discuss the predator-prey model using Holling type II functional response with the time delay in facultative stabilization pond. In this research, we discuss the predator-prey model using Holling type II functional response with the time delay, determining the equilibrium point, the stability analysis of predator-prey model using Holling type II functional response with the time delay and numerical simulation of the predator-prey model using Holling type II functional response with the time delay. The method used to analyse the problem is by literature study. The steps used are the development of a mathematical model of change of dissolved oxygen concentration, phytoplankton and zooplankton, mathematical equation solving algorithm, field data, simulation using Maple and Mathematica 9 software and validation with research.